Campus Sustainability : Student’s Perception on Campus Physical Development Planning in Malaysia - Nurakmal, Abdullah@ Goh Tuo Ho; Abd-Razak, M. Z.; Che-Ani, A. I.; Mustafa, N.K.F. (Elsevier Science, Ltd., 2011)
Campus physical development plan is an effective tool to shaping campuses‟ life, especially among students to promote a sustainable living community. The purpose of this study is to asses and evaluates student‟s perception about the physical development planning of their campuses. The case study conducted in four public research university campuses. The quantitative and qualitative methods have been use in this study. Quantitative method involved data collection by using questionnaire distributed to 100 students for each campus. While the qualitative methods involved behavioural observation and visual study. The findings from qualitative methods clarified the quantitative data. The overall findings revealed that all campuses had a similar typical problem. However, there are differences about the extent or severity of the problems in each campus. The result shows that the most compact campus (USM) among these campuses, have a minimal problems in term of physical development planning that affect student‟s life compared to others campuses.